Интерпретация семантики и функционирования иноязычных элементов в художественном тексте: лингвистический и психолингвистический аспекты - Лаппо, Марина Александровна; Уразбекова, Алина Айжарыковна (SlavVaria, 2022)
Interpretation of semantics and functioning of foreign language ele-ments in fiction: linguistic and psycholinguistic aspects. The article analyzes the results of a psycholinguistic experiment devoted to the perception and un-derstanding of foreign-language elements of Polish origin. The regularities of the "alienness" degree interpretation of the presented word from the type of the presented borrowing (polonism, exoticism, inclusion) and the possibility of identifying its meaning in the context are established.